Routine HIV Testing among Providers of HIV Care in the United States, 2009 - McNaghten, A. D. (Public Library of Science, 2013)
In 2006, CDC recommended HIV screening as part of routine medical care for all persons aged 13–64 years. We examined adherence to the recommendations among a sample of HIV care providers in the US to determine if known providers of HIV care are offering routine HIV testing in outpatient settings. Data were from the CDC's Medical Monitoring Project Provider Survey, administered to physicians, nurse practitioners and physician assistants from June-September 2009. We assessed bivariate associations between testing behaviors and provider and practice characteristics and used multivariate regression to determine factors associated with offering HIV screening to all patients aged 13–64 years. Sixty percent of providers reported offering HIV screening to all patients 13 to 64 years of age. Being a nurse practitioner (aOR = 5.6, 95% CI = 2.6–11.9) compared to physician, age<39 (aOR = 1.9, 95% CI = 1.0–3.5) or 39–49 (aOR = 2.1, 95% CI = 1.4–3.3) compared with ≥50 years, and black race (aOR = 2.6, 95% CI = 1.2–6.0) compared with white race was associated with offering testing to all patients. Providers with low (aOR = 0.2, 95% CI = 0.1–0.3) or medium (aOR = 0.4, 95% CI = 0.2–0.6) HIV-infected patient loads were less likely to offer HIV testing to all patients compared with providers with high patient loads. Many providers of HIV care are still conducting risk-based rather than routine testing. We found that provider profession, age, race, and HIV-infected patient load were associated with offering HIV testing. Health care providers should use patient encounters as an opportunity to offer routine HIV testing to patients as outlined in CDC's revised recommendations for HIV testing in health care settings.